1943
DOI: 10.1021/ja01243a013
|View full text |Cite
|
Sign up to set email alerts
|

The Heat Capacity and Entropy, Heats of Transition, Fusion and Vaporization and the Vapor Pressures of Cyclopentane. Evidence for a Non-planar Structure

Abstract: Entropy of Cyclopentane 341 sum £(333/ ) + 2£(494/ ) + 2£(1058/ ), which fits the data over the entire experimental range of temperature. In both instances only the Debye function is of importance in the extrapolation of entropy. Table II Entropies at 298.16°K. (cal./dbg. mol.) MgaSiO* MgSiOs 0-50.12°K. (extrap.) 0.60 0.49

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(33 citation statements)
references
References 0 publications
6
27
0
Order By: Relevance
“…The sensitivity s of the heat-flux detector as a function of temperature was determined by the manufacturer through a series of calibration runs using the Joule effect in the working temperature interval of the calorimeter T = (180 to 1100) K. The results of several melting runs performed under the same conditions as our d.s.c. measurements with various recommended reference materials are reported in table 2 (columns 5 and 7), and the agreement with the selected literature data (34)(35)(36)(37)(38) was about 0.06 per cent for temperature and about 0.3 per cent for enthalpy.…”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…The sensitivity s of the heat-flux detector as a function of temperature was determined by the manufacturer through a series of calibration runs using the Joule effect in the working temperature interval of the calorimeter T = (180 to 1100) K. The results of several melting runs performed under the same conditions as our d.s.c. measurements with various recommended reference materials are reported in table 2 (columns 5 and 7), and the agreement with the selected literature data (34)(35)(36)(37)(38) was about 0.06 per cent for temperature and about 0.3 per cent for enthalpy.…”
Section: Methodssupporting
confidence: 80%
“…peak measured by the thermal (34) 2.295 ± 0.005 2.2953 ± 0.0004 (34) Water Aldrich 6 273.12 ± 0.18 273.15 (35) 6.057 ± 0.018 6.0017 (35) Cyclohexane Aldrich 5 279.43 ± 0.24 279.84 ± 0.05 (36) 2.643 ± 0.083 2.627 ± 0.007 (36) Naphthalene LGC 4 353.05 ± 0.14 353.39 ± 0.03 (37) 19.072 ± 0.045 19.05 ± 0.04 (37) Benzoic acid Fluka 4 395.03 ± 0.14 395.52 (38) 17.787 ± 0.075 18.00 ± 0.10 (38) a Uncertainties are expressed as twice the standard deviation of the mean. b Number of calorimetric runs.…”
Section: Methodsmentioning
confidence: 99%
“…In the insert of J/tool and 615 (24) J/tool. Our data for T, and AH are, within the given errors, in agreement with the values obtained by adiabatic precision calorimetry [25].…”
Section: Cyclopentanesupporting
confidence: 89%
“…The DSC was calibrated from the heat of transition (Ϫ87.06°C) 16 and melting point (6.54°C) 11 of cyclohexane as well as from the glass-transition temperature (T g ; Ϫ125°C) 17 of PDMS. The analysis was begun by equilibration at Ϫ150°C for 30 min.…”
Section: Triblock Pdms-ps-pdms Copolymersmentioning
confidence: 99%
“…, and the equilibrium expansion factor ␣ (0.017) is based on the extrapolation of literature data 16 based on an interfacial tension value of 5 dyne/cm 1 . This result is in agreement with other TEM studies reported for PDMS-PS-PDMS triblock copolymers.…”
Section: ϫ9mentioning
confidence: 99%